Muscle contracture and passive mechanics in cerebral palsy - Lieber, Richard L. (J Appl Physiol (1985), 2019)
Skeletal muscle contractures represent the permanent shortening of a muscle-tendon unit, resulting in loss of elasticity and, in extreme cases, joint deformation. They may result from cerebral palsy, spinal cord injury, stroke, muscular dystrophy, and other neuromuscular disorders. Contractures are the prototypic and most severe clinical presentation of increased passive mechanical muscle force in humans, often requiring surgical correction. Intraoperative experiments demonstrate that high muscle passive force is associated with sarcomeres that are abnormally stretched, although otherwise normal, with fewer sarcomeres in series. Furthermore, changes in the amount and arrangement of collagen in the extracellular matrix also increase muscle stiffness. Structural light and electron microscopy studies demonstrate that large bundles of collagen, referred to as perimysial cables, may be responsible for this increased stiffness and are regulated by interaction of a number of cell types within the extracellular matrix. Loss of muscle satellite cells may be related to changes in both sarcomeres and extracellular matrix. Future studies are required to determine the underlying mechanism for changes in muscle satellite cells and their relationship (if any) to contracture. A more complete understanding of this mechanism may lead to effective nonsurgical treatments to relieve and even prevent muscle contractures.